Knowledge and the mathematical properties of communication. (19th April 2004) - James, Roger
This paper looks at some of the fundamental mathematical properties of communications. Knowledge is, we know, the property of a group of communicating agents yet little consideration is given to the features of these communications in the context of a group. Shannon & Weavers's landmark book, The Mathematical Theory of Communication, explored the properties of the information content within communication. This paper builds on this work by investigating the properties of communications within the ecology of Knowledge agents. The paper aims to feature some of the communication curiosities validated by mathematics and demonstrated in the physical world. These simple, but elegant, phenomena must be present in the more complex systems studied as KM systems and are required to build a substantial representation of knowledge in the internet age.